Relapse after recovery from acute malnutrition - Bliznashka, Lilia (Elsevier, 2025)
Globally, severe acute malnutrition affects 13·6 million children.1 The WHO-endorsed community-based management of acute malnutrition (CMAM) model is effective in achieving high recovery. However, there is increasing recognition that relapse after recovery is a problem, with a growing number of studies aiming to understand and quantify relapse burden and risk factors.2,3 Knowledge gaps remain in our understanding of the problem and its drivers due to methodological issues, lack of control groups, and inconsistent reporting.